2008
DOI: 10.1002/ppul.20800
|View full text |Cite
|
Sign up to set email alerts
|

Lag effect of particulate air pollution on lung function in children

Abstract: Summary. We assessed the relationship between particle air pollution and changes in lung function in children as measured by spirometry over time. Data were collected from air pollution and family health examinations of 181 subjects, aged 9-19 years, in a Korean community. The children performed lung function tests, and their height and weight were measured. Their parents responded to an interview regarding the children's history of disease. Data on air pollution were obtained from the Environmental Management… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…69 Outdoor levels of PM 10 and PM 2.5 have been related to acute reductions in FEV 1 and FVC, observed either within the same day, a few hours after exposure, or days after exposure (lag response). [70][71][72] In contrast, recent pooled analyses of cross-sectional studies in 12 countries did not reveal any association between PM 10 exposure and lung function in children. 73 Understanding the chronic respiratory health effects of outdoor air pollutants is more complex.…”
Section: Lung Functionmentioning
confidence: 80%
“…69 Outdoor levels of PM 10 and PM 2.5 have been related to acute reductions in FEV 1 and FVC, observed either within the same day, a few hours after exposure, or days after exposure (lag response). [70][71][72] In contrast, recent pooled analyses of cross-sectional studies in 12 countries did not reveal any association between PM 10 exposure and lung function in children. 73 Understanding the chronic respiratory health effects of outdoor air pollutants is more complex.…”
Section: Lung Functionmentioning
confidence: 80%
“…All, except two, studies investigated school-aged asthmatic and/or symptomatic children, while the remaining two considered infants and toddlers (Andersen et al 2008b;Coneus & Spiess, 2012). Most of the studies observed positive associations between short-term exposure to NO 2 (or nitrogen oxides) for different lags and respiratory symptoms, such as coughing and wheezing (O'Connor et al, 2008;Escamilla-Nuñez et al, 2008;Andersen et al, 2008b), as well as for exhaled nitric oxide (Sarnat et al, 2012) and also for pulmonary function decrease (O'Connor et al, 2008;Liu et al, 2009;Castro et al, 2009;Dales et al 2009;Min et al, 2008;Yamazaki et al, 2011;Ma et al, 2008) in children, although not all of them were statistically significant (Dales et al, 2009). One article reported numerical data only for PM (Min et al, 2008).…”
Section: Panel Studiesmentioning
confidence: 99%
“…A PubMed search identified 11 new articles: 6 from the Americas (Sarnat et al, 2012;O'Connor et al, 2008;Escamilla-Nuñez et al, 2008;Liu et al, 2009;Castro et al, 2009;Dales et al, 2009), 2 from Europe (Andersen et al, 2008b;Coneus & Spiess, 2012), and 3 from Asia (Min et al, 2008;Yamazaki et al, 2011;Ma et al, 2008). All, except two, studies investigated school-aged asthmatic and/or symptomatic children, while the remaining two considered infants and toddlers (Andersen et al 2008b;Coneus & Spiess, 2012).…”
Section: Panel Studiesmentioning
confidence: 99%
“…This weak association supports our findings, where we adjusted rigorously for potential confounders (e.g., living district, asthma status of the child), and found only associations of FVC and FEV 1 one year before the lung function measurement within the overall population. For the lagging effect of PM on lung function, the analysis was done by reviewing previous studies and found that more attention had been paid to the short-term acute effect (54,55), while fewer studies on the long-term effect can be referred to. Our study suggests that ADD may be used in future studies addressing the effects of long-term air pollution exposure.…”
Section: Discussionmentioning
confidence: 99%